Let 'the number' be A.
9 is added to twice a number... so...
9 + 2A
this ^ sum is multiplied by 6
6(9+2A)
This ^ is equal to to the number times by 7 plus 14... so...
6(9+2A) = 7A + 14
Now we expand the brackets, by multiplying both the 9 and the 2A by the 6 that is outside the brackets.
6x9= 54 and 6x2A=12A
so 12A + 54 = 7A + 14
we must get all the 'A' values on the left and all the other numbers on the right of the equal sign. when you swap sides you change the sign...
12A - 7A = 14 - 54
5A = -40
so A = (-40) divided by 5
(-40) ÷ 5 = -8
so the number is -8